Characteristic of Mineral Alteration of Geothermal in Endut Mount Based on Petrography, Spectra, XRD, and MeB methods - Patonah, Aton; Ramadhani, Rifqi Fadhil; Nurdin, Nizar M (Journal of Geoscience, Engineering, Environment, and Technology, 2026)
Endut Mount is one of the geothermal prospect locations in Indonesia. In order to optimize the geothermal potential of the research area, it is necessary to conduct research on geothermal characteristics. One such study is the examination of altered minerals in geothermal manifestations. The primary objective of this research is to conduct alteration investigations utilizing coring data obtained from the drilling of Well 1 by petrography, MeB, Spectra, and XRD method approaches. The result of the research shows that the lithology of this Well is a product of Endut Mount activity, with an intensity ranging from medium to strong. The lithology is composed of altered tuff and altered andesite breccia, which are a product of the Pleistocene period, and altered volcanic breccia and altered tuff breccia, which are a product of the Miocene period. This lithology is based on the oldest to the youngest succession. The alteration assemblages in Well 1 are classified into two zones based on the assemblage of alteration minerals: the illite-chlorite±epidote zone, which is located at a depth of 9.7– 40.9 MD, and the smectite-sericite-chlorite-epidote zone, which is located at a depth of 40.9 – 111.15 MD. The type of alteration in Well 1 is propylitic, with a neutral pH and a temperature range of 200oC to 300oC, as indicated by the mineral composition and alteration zone. This alteration zone has the potential to function as a reservoir zone.